Chromosomal evolution of tribe Oryzomyini (Rodentia: Cricetidae: Sigmodontinae) - do Nascimento Moreira, Camila [UNESP]; Percequillo, Alexandre Reis; Ferguson-Smith, Malcolm Andrew; Yonenaga-Yassuda, Yatiyo; Ventura, Karen (Springer Nature, 2022)
Oryzomyini is the most diverse tribe of subfamily Sigmodontinae, comprising 30 genera and 147 extant species. Cytogenetic studies on Oryzomyini reflect this diversity, revealing an exceptional range of karyotype variability, with chromosome numbers ranging from 2n = 16 to 2n = 88. In addition, some species exhibit autosomal and sex chromosomal polymorphisms, as well as the presence of B chromosomes. In the search for a more detailed understanding of the processes involved in karyotype diversification of Oryzomyini, we performed a genome-wide comparative study using chromosome probes of the entire chromosome set of Holochilus nanus and some autosomes of Oligoryzomys moojeni on metaphases of 15 species of Oryzomyini, in addition to one species of tribe Thomasomyini. We also performed a phylogenetic analysis of these species using chromosome painting data. The results show complete chromosome homology among the autosomal complement of species of Oryzomyini with the presence of pericentric inversions or centromeric shifts, paracentric inversion, Robertsonian rearrangements, tandem fusions/fissions, and translocations involved in the karyotype evolution of the tribe. In addition, sex chromosomes of these species present a homologous region between all analyzed species with amplification of the species-specific heterochromatin. The use of two different approaches to perform a phylogenetic analysis based on chromosome painting data revealed which one is more trustworthy and presents results similar to the findings obtained by molecular and morphological analyses. Finally, we propose that chromosomal diversity of the tribe Oryzomyini is promoted by genomic elements, such as repetitive DNA, that trigger the karyotype variability of these rodents.
Keywords: Chromosomal phylogeny; Karyotype evolution; Neotropical rodents; ZOO-FISH